System Application of Genetic Algorithm for Scheduling Optimization Study Using Java (Case Study : Department of Computer System UNTAN) - Fatma Agus Setyaningsih (Institut Teknologi Sepuluh Nopember, 2014)
cheduling of lecture in a university is a college activities into the work place and time that there is room in such a way so as to minimize the violation of the scheduling problems of a lecture. Problems that are often referred to as the University timetabling problem ( UTP ) is, requires a lot of consideration include the number of students, number of teachers who are not proportional to the number of courses, the amount of space used, as well as lecture predetermined time. Scheduling lectures with the automation system is very important because it can save you hours of work and provide optimum solutions in a short time, which can increase productivity, the quality of teaching and learning, and quality of service. One method that can be used to complete the course scheduling problem is a genetic algorithm approach. Genetic algorithm is an optimization tool that models the principles of evolution. Genetic algorithm is able to find a globally optimum solution in the search space is very complex. By using an initial population of solutions is encoded and selected based on its quality, and then used to create a new population using crossbreeding and mutation process of the initial individuals. Evaluation function is used to calculate the hard constraints and soft constraints can be met. This study discusses the scheduling college located in Department of Computer Systems Untan. The purpose of study is to optimize the college scheduling and to make easier the scheduling job with make a college scheduling software